2022
DOI: 10.3389/fenvs.2022.1084632
|View full text |Cite
|
Sign up to set email alerts
|

ESG performance and corporate value: Analysis from the stakeholders’ perspective

Abstract: Based on the panel data of China’s A-share non-financial listed enterprises from 2011 to 2020, we empirically explore whether EGS performance can significantly promote corporate value and how to promote it, from the stakeholders’ perspective. We find that: 1) ESG performance significantly improves corporate value. 2) Both media attention and analyst coverage play an intermediary role in the impact of ESG performance on corporate value. 3) Further analysis of the single dimension of ESG illustrates that Environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…The existing literature on ESG performance focuses on the economic consequences of ESG performance. Studies have found that improving ESG performance can enhance financial performance and firms' value [49][50][51][52], reduce accrued surplus management [55], alleviate financing constraints [56,57], improve customer stability [58], reduce corporate risk [62], etc. Fewer studies have focused on the factors influencing ESG performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature on ESG performance focuses on the economic consequences of ESG performance. Studies have found that improving ESG performance can enhance financial performance and firms' value [49][50][51][52], reduce accrued surplus management [55], alleviate financing constraints [56,57], improve customer stability [58], reduce corporate risk [62], etc. Fewer studies have focused on the factors influencing ESG performance.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the economic consequences of ESG performance, considerable research has found that improving ESG performance can contribute to financial performance growth and enhance firm value [14,15,[49][50][51][52]. Profitability is one of the most critical indicators of a company and is related to shareholders' equity, long-term liabilities, provisions, deferred income within one year, total liabilities, working capital, and current assets [53].…”
Section: Esg Performancementioning
confidence: 99%
“…The study highlights that ESG and CSR activities are closely associated with a company’s market characteristics as well as with its risks, performance, and value. Zheng et al 20 reported that ESG performance significantly enhanced the corporate value of listed companies, particularly through the mediating roles of media attention and analyst coverage. ESG factors are crucial risk factors for firms.…”
Section: Related Workmentioning
confidence: 99%
“…Traditional methods of evaluating corporate sustainability. From the perspective of social sustainable development, the Environmental, Social, and Governance (ESG) assessment stands out as the most widely accepted approach [9]. A notable gap exists in recognized evaluation methods that focusses on the internal sustainable development of businesses.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%